OBSTETRIC HEMORRHAGES AS THE MAIN CAUSE OF CRITICAL CONDITIONS AND MATERNAL MORTALITY - Maria N. Surina; Tatiana Y. Marochko (Фундаментальная и клиническая медицина)
Maternal mortality is now established as a key health indicator in women of reproductive age. Moreover, it can be recognized as an indicator of the country healthcare system since it reflects both the availability and quality of prenatal and obstetric care. The high rate of obstetric hemorrhage (OH)-related mortality reflects the poor quality of medical care and indicates the possibility to reduce maternal deaths. OH, particularly postpartum hemorrhages, remain a significant cause of maternal mortality worldwide. OH may cause critical conditions accompanied with massive blood loss and altered hemostasis. In recent years, a «near miss» conception became widely applied in obstetrics, particularly in regard to OH. This provides additional advantages and increases potential for decreasing maternal mortality. World Health Organization systematic review indicated three distinct approaches for identifying severe maternal morbidity: 1) the definition of criteria for clinical complications such as severe pre-eclampsia and hemorrhage; 2) admission of the patient in the intensive care unit, performance of hysterectomy or massive blood transfusion; 3) correction of organ dysfunction (shock or respiratory distress). It is important to develop standardized criteria for determining «near miss» cases to apply this principle as a research tool and improve the quality of obstetric care.